2012
DOI: 10.1016/j.jeurceramsoc.2011.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Electric charge trapping, residual stresses and properties of ceramics after metal/ceramics bonding

Abstract: To cite this version:Lamine Hattali, Nadir Mesrati, Daniel Tréheux. Electric charge trapping, residual stresses and properties of ceramics after metal/ceramics bonding. Journal of the European Ceramic Society, Elsevier, 2012, 32, pp.717-725. hal-00657384 Electric charge trapping, residual stresses and properties of ceramics after metal/ceramics bonding AbstractThe use of ceramic components in electrical engineering and mechanical applications is rapidly increasing. Most of these applications require the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The Scanning Electron Microscope Mirror (SEMM) method is frequently employed in study of electrical properties (charge trapping/detrapping, flashover, and electric breakdown) of insulating material (polymers, ceramics, …) and it has much interest because of its importance in technology and industry [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The Scanning Electron Microscope Mirror (SEMM) method is frequently employed in study of electrical properties (charge trapping/detrapping, flashover, and electric breakdown) of insulating material (polymers, ceramics, …) and it has much interest because of its importance in technology and industry [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The connection of ceramic and metal to obtain high-quality joints will achieve the optimization of the respective properties of ceramics and metals and combine the advantages of high hardness, high strength, and easy processing of metals [5]. Therefore, the application scope of engineered ceramics can be expanded [6,7], and reliable joints of ceramics and metals should be assessed for successful manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Xin et al [6] revealed that a layer of titanium film plated on the surface of Al 2 O 3 would increase the strength of the soldered joint. Fan et al [7], Wang et al [8] and Hattali et al [9] measured the residual stress of the soldered structure with Al 2 O 3 ceramics and different materials such as Y-TZP and SiC ceramics. Niu [10] and Zhong [11] also performed relevant experiments on Kovar alloy.…”
Section: Introductionmentioning
confidence: 99%